U.S. Macroeconomic news and low-frequency changes in small open economies' bond yields - Bingxin Ann Xing; Bruno Feunou; Morvan Nongni-Donfack; Rodrigo Sekkel (Bank of Canada, 2024)
This paper investigates the importance of U.S. macroeconomic news in driving low-frequency fluctuations in the term structure of interest rates in Canada, Sweden and the United Kingdom. We follow two complementary approaches: First, we apply a regression-based framework that aggregates the impact of daily macroeconomic news on bond yields to a lower quarterly frequency. Next, we estimate a macro-finance affine term structure model linking the daily news to lower-frequency changes in bond yields and their expectations and term premia. Both approaches show that U.S. macroeconomic news is an important source of lower-frequency quarterly fluctuations in bond yields in these small open economies-even more important than the respective countries' domestic macroeconomic news. Furthermore, the macro-finance model shows that U.S. macroeconomic news is particularly important to explain low-frequency changes in the expectation components of the nominal, real and break-even inflation rates.
Keywords: E43; E44; E47; G14; 330; Central bank research; Econometric and statistical methods